Outcomes of horses treated with removal of a laryngoplasty prosthesis. Issue 4 (4th January 2019) - Fitzharris, Laura E.; Lane, J. Geoffrey; Allen, Kate J.
Abstract: Objective: To determine the proportion of horses treated by laryngoplasty prosthesis removal (LPR) for complications associated with prosthetic laryngoplasty (LP), the reason for LPR, and the outcome of horses undergoing LPR to manage iatrogenic coughing/dysphagia. Study design: Retrospective study. Sample population: Client‐owned horses treated with LP (n = 1202) and LPR (n = 58). Methods: Clinical case records were reviewed to determine the number of horses treated with LP and LPR by the same surgeon. Historical, clinical, endoscopic, and surgical data were extracted for those horses undergoing LPR. Long‐term outcome was assessed by questionnaire. Results: The proportion of horses treated with LP and subsequently treated with LPR by the same surgeon was 3.5% (42/1202). Coughing/dysphagia was the reason for LPR in 90% (52/58) of horses. Sufficient follow‐up to determine outcome in horses undergoing LPR for coughing/dysphagia was available in 32 horses. Arytenoid abduction grade at the time of LPR did not influence clinical response ( P = .416). Presenting clinical signs resolved after LPR in 21 of 32 (66%) horses, and 24 of 32 (75%) horses returned to exercise. Conclusion: Coughing/dysphagia was the most common reason for LPR. Clinical signs improved in most horses after LPR. Clinical significance: Laryngoplasty prosthesis removal can be a useful treatment option for horses affected with unmanageable coughing/dysphagia caused by LP.